2009
DOI: 10.1541/ieejfms.129.62
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Applications of Pulsed Power Technology

Abstract: A review of mainly the past two years is undertaken of the industrial applications of pulsed power. Repetitively operated pulsed power generators with a moderate peak power have been developed for industrial applications. These generators are reliable and have low maintenance. Development of the pulsed power generators helps promote industrial applications of pulsed power for such things as food processing, medical treatment, water treatment, exhaust gas treatment, ozone generation, engine ignition, ion implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The DBD generated ozone has been applied in treatment of polluted water, decomposition of exhaust gas and surface modification. [22][23][24] Analysis & measurements Chemical and Biological Oxygen Demand (COD &BOD)…”
Section: Ozone Generationmentioning
confidence: 99%
“…The DBD generated ozone has been applied in treatment of polluted water, decomposition of exhaust gas and surface modification. [22][23][24] Analysis & measurements Chemical and Biological Oxygen Demand (COD &BOD)…”
Section: Ozone Generationmentioning
confidence: 99%
“…THE application of sub-microsecond bipolar HV pulses is, nowadays, widely seen in areas such as food processing, medical treatment, waste water and exhaust gas processing [1][2][3][4][5]. To achieve flexible, efficient and reliable bipolar modulators, numerous techniques, from the use of solid-state technology to pulse forming lines, PFL, are applied.…”
Section: Introductionmentioning
confidence: 99%
“…DBD has been widely used for generation of activate radicals and excited species such as O, H, O 3 , N 2 þ , and OH, which are generated by dissociation and ionization of the ambient gases as a result of energy transfer from energetic electrons to the gas molecules. 23) DBD-generated ozone has been successfully applied to treatment of polluted water, decomposition of exhaust gas and surface modification. [23][24][25] Okpalugo et al demonstrated oxidation of CNTs using a DBD reactor and showed increase of oxygen-rich functional groups such as -COO À on CNTs surface.…”
Section: Introductionmentioning
confidence: 99%
“…23) DBD-generated ozone has been successfully applied to treatment of polluted water, decomposition of exhaust gas and surface modification. [23][24][25] Okpalugo et al demonstrated oxidation of CNTs using a DBD reactor and showed increase of oxygen-rich functional groups such as -COO À on CNTs surface. 26) However, they did not investigate relationship between SWCNT functionalization and DBD-generated ozone.…”
Section: Introductionmentioning
confidence: 99%